2019
DOI: 10.14254/2071-8330.2019/12-1/11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of tourism sector as a viable response to South Africa’s growth and development challenges

Abstract: Tourism is one of the top-three foreign revenue generating economic sectors globally, representing the total of 7% in the overal global exports. Overall weak economic and sectoral performance stresses the need for a strong alternative economic sector development so that to support traditional growth sectors which could potentially increase economic growth and development in South Africa. The aim of this study was to analyse the impact of the tourism sector on both economic growth and development in South Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Outcomes from the time-varying coefficients model showed that tourism receipts have positive predictive power over GDP. A study of the relationship between tourism and GDP growth carried out by Van der Schyff et al (2019), using cointegration and VECMs, also confirmed the existence of a long-run relationship between both variables in South Africa.…”
Section: Literature Reviewmentioning
confidence: 65%
“…Outcomes from the time-varying coefficients model showed that tourism receipts have positive predictive power over GDP. A study of the relationship between tourism and GDP growth carried out by Van der Schyff et al (2019), using cointegration and VECMs, also confirmed the existence of a long-run relationship between both variables in South Africa.…”
Section: Literature Reviewmentioning
confidence: 65%
“…According to Van Der Schyff et al (2019), TRM makes around 7% of the total global revenue. Tourism led ECO has gained lots of attention in recent times, there are several empirical and theoretical studies on to 2017 and found a long-run nexus between TRM and EG.…”
Section: Sustainable Tourism and Economic Growthmentioning
confidence: 99%
“…Cooperation within a particular tourism-oriented supply chain is mainly focused on integrating the available resources and increasing the likelihood of the successful operation of individual suppliers [9]. Relations occurring within the scope of a tourism-specific supply chain can be characterized by taking advantage of the following criteria: Approach to a tourist as a member of the supply chain (direct, indirect) [10] Business goals resulting from relations between entities operating on the tourism-oriented market are directed towards the increase of generated income, cost reduction, maintaining relations with clients, increasing competitiveness, boosting efficiency, and ensuring satisfactory human resource management. The occurring changes and goals connected with them are affected by information and communication technologies (ICT) [11] that allow for direct contact between partners using a two-way circulation of information in real-time.…”
Section: Literature Reviewmentioning
confidence: 99%